Nucleus Drop or Intraocular Lens Drop Underwent Pars Plana Vitrectomy due to Complication of Cataract Surgery - Noviana Kurniasari Vivin; Ari Djatikusumo; Elvioza Elvioza; Gitalisa Andayani; Anggun Rama Yudantha; Mario Marbungaran Hutapea; Andi Arus Victor (Indonesian Vitreoretinal Society, 2019)
Abstract Background: The incidence of nucleus drop or intraocular lens (IOL) drop as the complication of phacoemulsification increases due to the increased frequency of phacoemulsification. Pars plana vitrectomy (PPV) followed by endofragmentation and secondary IOL implantation is the choice of procedure for management. This study aims to determine the frequency, outcomes, and complication of PPV in the case of nucleus drop or IOL drop in the Department of Ophthalmology, Fakultas Kedokteran Universitas Indonesia – Rumah Sakit Cipto Mangunkusumo (FKUI-RSCM) Methods: This study is a retrospective descriptive study conducted in the Vitreoretinal Division of the Department of Ophthalmology, FKUI - RSCM. Research data was taken from the medical records of all nucleus drop or IOL drop patients underwent PPV in January 2017-December 2017. Results: There were 19 cases studied. The incidence of nucleus drop occurred in phacoemulsification surgery techniques (94.7%) and ECCE techniques (5.3%). Vitrectomy surgery was performed ≤2 weeks in 31.6% and >2 weeks in 68.4% after the patient first arrived at the vitreoretinal clinic. Most pre-PPV visual acuity was 1/60-6/60 (47.1%). In the final follow-up, visual acuity improved from 6/45 to 6/6 occurred in 42.2% of cases. Complication after PPV and secondary IOL implantation include elevated IOP (10.5%), IOL decentration (5.3%), corneal decompensation (5.3%), macular edema (5.3%), and retinal detachment (5.3%). Conclusion: Nucleus drop or IOL drop generally occurs in phacoemulsification cataract surgery techniques. Improved visual acuity was achieved after PPV and secondary IOL implantation at the end of the follow-up period. Most common post-PPV complication is elevated IOP.